Knowledge and practice on vaping among undergraduate students in a private university in Kajang - Sia, Chee Yan (2023)
BACKGROUND: Vaping is generally perceived as more attractive than traditional cigarettes due to factors like accessibility, affordability, stylish designs, and ease of use. However, many studies found that misconceptions exist, such as perceiving vaping as less harmful and less addictive than smoking, even as a smoking cessation aid. These misunderstandings have contributed to a surge in usage, particularly among young people, despite associated health risks.